First-year university biology students' difficulties with graphing skills - Kali, Horatius Dumisani (My University, 2006)
Based on the perceived need for improved graphing skills of students at first-year university level, two lecturers wanted to produce a web-based computer programme to improve first-year university biology students’ ability to construct and interpret graphs. Prior to designing and developing the package, however, it was important to establish whether there was a need for such a programme, and what might need to be included. The investigation to establish this provided the research described in this research report. A situation analysis was conducted to establish the nature and extent of the problems of graphing skills discussed anecdotally in the staff room of biology departments at a number of institutes. The ultimate intention (beyond this study) was to determine whether the problems were extensive and serious enough to warrant developing supplementary teaching materials to teach graphing skills. All lecturers (n = 5) and teaching assistants (n = 4) involved in using or teaching graphing skills to first-year biology students at one university were identified and interviewed. The purpose of the interviews was to establish the problems they believed are exhibited by their first-year students (with reference to graphing skills), and the nature and extent of current teaching of such skills in their first-year courses. In order to triangulate the information on student’s problems an item analysis was conducted of all questions incorporating graphs in two mid-year examination papers (n = 478 and n = 65), and students were observed during a practical session (n = 43). Results revealed that students experienced fewer problems with interpreting graphs than with graph construction. Of the four categories of graph interpretation problems identified by the teaching staff, the most popular category was students inability to describe quantitatively what the graph is showing (4 teaching staff). This was confirmed in the question paper analysis when 58% of the medics students (n=478) were unable to answer correctly one question involving several interpretation skills. No specific skills for graph interpretation were observed as being a problem in the College of Science question paper (n=65). Observations showed interrelating graphs as the biggest problem (5 students out of 43). Five categories for problems with graph construction were identified by the teaching staff. The most commonly mentioned problem (4 teaching staff) was identifying or plotting variables, whereas class observation revealed scaling axes as the most problematic skill shown by students (15 out of 43). In the exams, 80% of the medics students could not correctly answer one question requiring multiple skills including identifying variables, and 56% could not correctly answer another question that required skills that also involved identifying variables. The College of Science question paper revealed that 85% of the students could not supply the units of measurement for the y axis. A needs analysis was conducted to establish how the lecturers thought graphing skills should be taught and who should teach the skills. This information was needed to provide suggestions (from education “experts”) about what could be included in the computer programme to be developed subsequent to the research study, and how the teaching could best be done. Four members of the teaching staff said it was important to give students a lot of exercises to practice the skills and five members of the teaching staff said it was the responsibility of the university tutors or lab staff to teach graphing skills.
Student Number : 0110601M - MSc research report - Faculty of Science
Keywords: graphing skills; first-year university level; biology students; construct and interpret graphs; situation analysis; problems; needs analysis